Pernikahan Dini dan Reproduksi Budaya Patriarki di Solear, Kabupaten Tangerang - sabilillah, syahid (Saskara : Indonesian Journal of Society Studies, 2024)
Marriages that occur in the early age group, run with an interpretation of the limitations of the couple to create equality in the family. This research aims to find out the involvement of the phenomenon of early marriage in reproducing patriarchal culture, especially in the household and to find out the form of patriarchal culture reproduced in households born from early marriage in Solear, Tangerang Regency. This research uses a descriptive qualitative research method with a case study approach. This research was conducted based on Kate Millet's concept of patriarchy and Randall Collins' gender stratified family. The results of this study show that the phenomenon of early marriage in the Solear Subdistrict area shows the process of reproducing patriarchal culture through the institutionalization of patriarchal social values in the family, thus ultimately giving birth to four (marginalization, subordination, stereotyping, and double burden) of the five forms of gender injustice initiated by Mansour Fakih. However, the research findings also show that the reproduction of patriarchal culture comes from those who marry at the ideal age.